Gender and Islam in Africa: Rights, Sexuality, and Law By Margot Badran, ed. (Washington, DC: Woodrow Wilson Center Press, 2011. 324 pages.) (American Journal of Islam and Society, 2012)
Gender and Islam in Africa is a great contribution to the scholarship onAfrican women. The contributors, all of whom come from different disciplines,seek to elevate the status of women by promoting gender equality,human rights, and democracy in androcentric African societies. They appealfor more women to participate in the reshaping and reforming of women’sroles; assert that women were part of Africa’s development; and maintainthat male religious scholars who interpret Islamic religious texts in a way designedto relegate women to second-class status, as opposed to Islam, are theprimary cause of women’s predicaments. This work is divided into threemajor sections: “Women Re/produce Knowledge,” “Re/constructing Women,Gender, and Sexuality,” and “Shari‘ah, Family Law, and Activism.” The contributorscite many examples of female scholars, among them Nana Asma’uand Malama Aishatu Dancandu, and their production of knowledge beforeand after colonialism.